(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACT Objective: To determine the radiological and functional outcome of dual plating of tibial plateau Schatzkar type VI fracture. Methods: This descriptive study was conducted in Orthopaedic B unit Lady Reading Hospital Peshawar from February 2015 to August 2017. All patients with type VI tibial plateau fractures fulfilling the inclusion criteria were enrolled. All were treated with dual platting with double incisions. Minimum follow up period was one year. Outcome was assessed radiologically by Modified Rasmussen Assessment Criteria and functionally by Oxford Knee Scoring system. Results: A total of 42 patients with mean age 36.6 years(range 18-52 years) Â±SD 7.7 were treated with dual plating. Male patients were 33(78.5%) while female patients were 9(21.4%). The radiological evaluation at one-year follow up produced excellent results in 33(78.5%) patients, good in 7(16.6%) and fair in 2(4.7%) patients. Functional outcome was excellent in 34(80.9%) patients, good in 5(11.9%), fair in 2(4.7%) and poor in 1(2.3%). 5(11.9%) patients developed superficial wound infection while 2(4.7%) patients suffered from deep wound infection. No delayed union, non-union or deformity was reported. Conclusion: Schatzker type VI fractures treated with open reduction and dual plating produce excellent and good radiological and functional outcome in majority of patients. We therefore recommend dual plating with two incisions as treatment of choice for the treatment of such fractures.